Pengaruh Gaji, Penilaian Kinerja dan Budaya Organisasi Terhadap Kinerja Karyawan (Studi Pada TPST 3R Mulyoagung Bersatu) - Satria, Lucky Yoga; Basalamah, Muhammad Ridwan; Athia, Ita (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract   This research aims to determine and analyze the influence of salary, performance assessment and organizational culture on employee performance at TPST 3R Mulyoagung Bersatu. The population in this study were employees at TPST 3R Mulyoagung Bersatu. The data collection method in this research used a questionnaire with a sample size determined using a saturated sampling technique and the results obtained were 69 respondents. Data testing techniques used in this research include validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, f test, t test, and coefficient of determination test (Adjusted R2). The results of this research simultaneously show that salary, performance appraisal and organizational culture have a significant influence on employee performance. Partially, salary has no significant influence on employee performance, performance appraisal has a significant influence on employee performance, and organizational culture has no significant influence on employee performance. Keywords: Salary, Performance Assessment, Organizational Culture and Employee Performance.